Curso de licenciatura em educação do campo: a perspectiva dos discentes egressos sobre o processo de formação - FRUTUOSO, Fagner Soares (2021)
Education in the countryside has been gaining prominence in the academic field over the years for showing fruit of resistance against the oppression of men and women in the countryside, of resistance to illiteracy and of the appreciation for social equality. In this perspective, this work is the result of a research that aimed to analyze the research subjects' conceptions about the formation process in the Degree Course in Rural Education - Natural Sciences, offered by the Federal University of Pará, Altamira Campus. The data were collected from an interview, via online form, carried out with the graduates of the course and for that purpose, Information and Communication Technologies (ICTs) were used. Data analysis was carried out following the steps of content analysis to make a comparison between the responses of the research subjects and the proposals of the pedagogical project of the analyzed course. The results point to a good training process, since most of the interviewed graduates pointed out that the course was essential for personal and professional training to work both in the field and outside.